2020
DOI: 10.1016/j.nbd.2020.105064
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin treatment of repetitive behavioral deficits in the Cntnap2 mouse model of autism spectrum disorder

Abstract: Nighttime light pollution is linked to metabolic and cognitive dysfunction. Many patients with autism spectrum disorders (ASD) show disturbances in their sleep/wake cycle, and may be particularly vulnerable to the impact of circadian disruptors. In this study, we examined the impact of exposure to dim light at night (DLaN, 5 lx) in a model of ASD: the contactin associated protein-like 2 knock out ( Cntnap2 KO) mice. DLaN was sufficient to disrupt locomotor activity rhythms, exacerbate th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 79 publications
2
27
0
Order By: Relevance
“…2C, Table 2 ). We had previously shown that DLaN reduces social behavior in C57 mice (Wang et al, 2020), hence, the effect of the short λ illumination was examined on this behavior in the Opn4 DTA . In WT mice, the DLaN greatly reduced social interactions (57.4 ± 10%), while the mutant mice were resistant to this negative effect of night-time illumination (8.9 ± 8.2%, Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…2C, Table 2 ). We had previously shown that DLaN reduces social behavior in C57 mice (Wang et al, 2020), hence, the effect of the short λ illumination was examined on this behavior in the Opn4 DTA . In WT mice, the DLaN greatly reduced social interactions (57.4 ± 10%), while the mutant mice were resistant to this negative effect of night-time illumination (8.9 ± 8.2%, Fig.…”
Section: Resultsmentioning
confidence: 99%
“…It has been speculated that this exposure to DLaN via screens and other lighting sources could be detrimental to ASD populations. In support of this speculation, we previously reported that an animal model with a genetic risk factor associated with ASD (contactin associated protein-like 2, Cntnap2 ) shows reduced social preference and increased stereotypic grooming behavior after a 2-week exposure to DLaN (Wang et al, 2020).…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…Since a large proportion of people with neurodevelopmental disorders such as ASD are disturbed in their daily sleep/wake cycles ( Robinson-Shelton and Malow, 2016 ). In response to this phenomenon, researchers tried melatonin treatment in CNTNAP2 KO mice and found that it improved excessive grooming in mice ( Wang et al, 2020 ). Furthermore, MTHFR polymorphism was associated with an increased risk of ASD, and the offspring of Mthfr + / − mice ( Pu et al, 2013 ), whether wild-type or heterozygous, exhibited autism-like behaviors.…”
Section: Treatment and Intervention Of Repetitive Restricted Behaviorsmentioning
confidence: 99%
“…Recent findings demonstrate mental health has deteriorated as a result of the pandemic, evident through increased anxiety and depression and greater stress levels (8,9). Also, it has been suggested that susceptibility to viral infections may be more prevalent in autistic adults due to health vulnerabilities such as co-occurring complex physical and mental conditions and melatonin deficiencies (10)(11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%